Relation between functional connectivity and disability in multiple sclerosis: a non-linear model - Tommasin, Silvia; De Giglio, Laura; Ruggieri, Serena; Petsas, Nikolaos; Giannì, Costanza; Pozzilli, Carlo; Pantano, Patrizia (Journal of neurology, 2018)
Objective To characterize the relation between brain functional connectivity and disability in patients with multiple sclerosis; to investigate the existence of critical values of both disability and functional connectivity corresponding to exhaustion of functional adaptive mechanisms. Methods Hundred-and-nineteen patients with no-to-severe disability and 42 healthy subjects were studied via 3T resting state functional MRI. Out of 116 regions extracted from Automated Anatomical Labeling atlas, pairs of regions whose functional connectivity correlated with Expanded Disability Status Score were identified. In patients, mathematical modeling was applied to find the best models describing Expanded-Disability-Status-Score vs structural or functional measures. Functional vs structural models intersecting points were identified. Results Disability had direct linear relation with lesion load ( r = 0.40, p < 5E−6), inverse of thalamic volume ( r = 0.31 p < 1E−3) and functional connectivity in bi-frontal pairs of regions ( r > 0.40, p < 0.04), while being non-linearly associated with functional connectivity in cerebello-temporal and cerebello-frontal pairs of regions ( F > 1.73, p < 0.02). Structural vs functional models intersecting points corresponded to Expanded Disability Status Score of 3.0. 85% of patients scoring more than 3.0 showed functional connectivity in cerebello-temporal and cerebello-frontal pairs of regions below confidence intervals ( z = [2.28–2.88] 95% CI) measured in healthy subjects. Conclusions Functional brain connectivity changes may represent mechanisms of adaptation to structural damage and inflammation and may be not always clinically beneficial. Functional connectivity decreases in comparison with structural measure at Expanded Disability Status Score greater than 3.0, which may be critical and indicate exhaustion of compensatory mechanisms.